2017
DOI: 10.18178/ijiet.2017.7.6.903
|View full text |Cite
|
Sign up to set email alerts
|

Using m-Learning as an Effective Device in Teaching and Learning in Higher Education in Saudi Arabia

Abstract: Abstract-E-learning is the use of technology to enable students to learn at anytime and anywhere. E-learning might also include the provision of information, and training in a timely manner, as well as guidance from experts. Technology can effectively enable learners to learn at any place and any time. Mobile learning or m-learning is defined as Learning through multiple channels, using smart devices, through social networking and content. Mobile devices such as mobile phones, PDAs, and tablets such as iPads a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This finding is consistent with the study conducted by Moya et al [65], who observed that students expressed excitement and happiness when using mobile devices to access the Moodle application in a college course. It seems from these results that students are excited and happy to use mobile learning, as was found [66]. Students are comfortable using m-learning and enjoy it.…”
Section: Discussionsupporting
confidence: 62%
“…This finding is consistent with the study conducted by Moya et al [65], who observed that students expressed excitement and happiness when using mobile devices to access the Moodle application in a college course. It seems from these results that students are excited and happy to use mobile learning, as was found [66]. Students are comfortable using m-learning and enjoy it.…”
Section: Discussionsupporting
confidence: 62%
“…The second is commercial software, called Blackboard [15]. Blackboard includes several tools, such as learning and teaching activities, assignments, e-content, course organization, discussion board and virtual classroom [9] [26]. In addition, an LMS can be integrated with traditional educational methods to create blended learning.…”
Section: Learning Management Systems (Lms)mentioning
confidence: 99%
“…Conduct the initial study 2017 This study focuses on the best ways to incorporate YouTube into learning and how students view its use. The findings of this study demonstrate that students had favorable impressions of YouTube videos (Alkhalaf et al, 2017). Also conducted the second study (2018) the use of YouTube in teaching and its advantages in the educational activities are the main topics of this study.…”
Section: Introductionmentioning
confidence: 79%